Effect of lateral positioning on the bronchial cuff pressure of a left-sided double-lumen endotracheal tube during thoracic surgery: study protocol for a prospective observational study. Issue 3 (30th March 2019) - Kim, Eugene; Kim, In-Young; Byun, Sung-Hye
Abstract : Introduction: Correct pressure is important when using a double-lumen endotracheal tube (DLT), especially in thoracic surgery. An inadequate bronchial cuff pressure (BCP) can cause air leak and interfere with visualisation of the surgical field, whereas an excessive pressure BCP can lead to cuff-related complications. Based on several reports that cuff pressure could alter after a positional change when using an endotracheal tube, we hypothesise that a change from the supine position to the lateral decubitus position, which is essential for thoracic surgery, would affect the BCP of the DLT. Methods and analysis: This prospective, single-centre, observational study will enrol 74 patients aged 18–70 years undergoing elective lung surgery from September 2018 to April 2019. The primary outcome will be the change in the 'initially established BCP' (maximum BCP not exceeding 40 cm H2 O with no air leak in the supine position) after lateral decubitus positioning. BCP and air leak will be assessed in each patient position during inflation of the cuff with air in 0.5 mL increments from 0 to 3 mL. Secondary outcomes will include the incidence of BCP exceeding 40 cm H2 O after the initial established value and that of a change in the smallest bronchial cuff volume without air leak after a change to the lateral position. The relationship between the change in BCP and airway pressure, compliance and body mass index after lateral positioning will be investigated. Ethics and dissemination: The study will be conducted in accordance with the Declaration of Helsinki and supervised by the Daegu Catholic University Medical Center institutional review board (study approval number CR-18–111). All patients will receive information about the study and will need to provide written informed consent before enrolment. The results will be presented at an international meeting and published in a peer-reviewed journal. Trial registration number: NCT03656406 ; Pre-results.